Exopolysaccharide Productivity and Biofilm Phenotype on Oral Commensal Bacteria as Pathogenesis of Chronic Periodontitis - Yamanaka, Takeshi; Yamane, Kazuyoshi; Mashimo, Chiho; Nambu, Takayuki; Maruyama, Hugo; Leung, Kai-Poon; Fukushima, Hisanori (IntechOpen, 2012)
None